Characteristics and Assessment of Frailty as Risk Factor of Therapy-Related Acute Toxicities and Delayed Overall Treatment Time in Elderly Patients Treating with External Beam Radiation Therapy at Indonesia Top Referral Hospital - Octavianus, Steven; Handoko, Handoko; Permata, Tiara Bunga Mayang; Purwoto, Gatot; Adham, Marlinda; Panigoro, Sonar Soni; Setiati, Siti; Gondhowiardjo, Soehartati (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Older patients are at a higher risk of being frail. Frailty implies that even a minor stressor can have major negative implications on physical, psychological domains. Geriatric-8 (G-8) screening tool shows good screening properties for identifying vulnerable elderly patients with cancer. AIM: We, therefore, decided to investigate the utility of G-8 associated with acute toxicity and prolonged overall treatment time (OTT) in elderly cancer patients treated with radiotherapy (RT). MATERIALS AND METHODS: A prospective observational cohort study is performed. Eligible subjects are patients aged ≥60 years and were referred for curative or palliative RT. We use the G-8 questionnaire for consecutive patients before starting RT. We recorded acute toxicity and OTT and identified potential predictors. RESULTS: A total of 52 consecutive geriatric patients were included with an average age of 67 years. Of all those subjects, 21% had head-and-neck cancers, 29% gynecology cancers, 23% breast cancers, and 27% other cancers. According to the G-8, 65% of the patients were potentially frail. Toxicity Grade ≥3 was observed among 32% of subjects who were potentially frail according to the G-8 and 0% of the subject who was fit (p = 0.007). Prolonged OTT was observed in 61.8% of potentially frail and 27.8% of the subjects who were fit (p = 0.020). On multivariate analysis, only chemoradiation was strongly associated with acute toxicity Grade ≥3 odds ratio 11.1 (95% confidence interval 1.4–83.6; p = 0.019). CONCLUSION: The utility of G-8 in daily practice seems to be limited. Only concurrent chemoradiation was associated with acute toxicity. Future prospective studies should investigate whether the G-8 is a good predictor for other relevant clinical outcomes and survival in our local settings.